Pengaruh Pemberian Ekstrak Akar Pasak Bumi (Eurycoma longifolia Jack) Terhadap Motilitas Spermatozoa Tikus Wistar Jantan yang Terpapar Nikotin - Bimby Irenesia; Dewi Indayani (Universitas Methodist Indonesia, 2026)
Background: Men contribute to approximately 50% of infertility cases. Furthermore, around 40% of male infertility is attributed to idiopathic factors. Various factors that lead to male infertility include lifestyle choices such as smoking. Free radicals resulting from cigarette smoke can induce damage to deoxyribonucleic acid (DNA) and apoptosis of spermatozoa cells. Objective: To analyze the effect of giving pasak bumi root extract (Eurycoma longifolia Jack) on the spermatozoa motility of male Wistar rats exposed to nicotine. Method: Fifteen male rats were randomly divided into five groups, with each group consisting of three rats. Groups 1, 2, and 3 were administered nicotine at 1.0 mg/kg body weight (BW) and pasak bumi (Eurycoma longifolia Jack) root extract at doses of 50 mg/kg BW, 100 mg/kg BW, and 200 mg/kg BW, respectively. Group 4 was only given the nicotine preparation, while Group 5 served as the control group. All groups were provided ad libitum food and water for 48 days. On the 49th day, testicles were harvested, and motility examination was conducted. Data analysis was performed using one-way ANOVA. Results: There was an influence of pasak bumi root extract (Eurycoma longifolia Jack) administration at a concentration of 50 mg/kg BW/day on the spermatozoa motility of male Wistar rats exposed to nicotine. There was an effect of pasak bumi root extract (Eurycoma longifolia Jack) at a concentration of 100 mg/kg BW/day on the spermatozoa motility of male Wistar rats exposed to nicotine. There was an effect of pasak bumi root extract (Eurycoma longifolia Jack) at a concentration of 200 mg/kg BW/day on the spermatozoa motility of male Wistar rats exposed to nicotine. Conclusion: Pasak bumi root extract (Eurycoma longifolia Jack) has an impact on the spermatozoa motility of male Wistar rats exposed to nicotine.